ADHESIVE FOR CHIPBOARD AND ITS SYNTHESIS - Шайманова Рано; Khodzhamkulov S.Z.; Shaimanova Nargiza; Abdukayumov Abdurashid (Galaxy International Interdisciplinary Research Journal, 2022)
Due to their high reactivity, chemical versatility, and economic competitiveness, formaldehyde-based polycondensation adhesives are used in large quantities—up to 20 million metric tons in 2010—worldwide, primarily in the woodworking industry. Since the 1970s, formaldehyde emissions from its products have come under pressure and have steadily declined. The debate that began with the latest European CLP (classification, labeling and packaging) regulation, which came into force in 2016, has intensified again, classifying formaldehyde as a carcinogenic category 1B compound. Given the potential and even stronger future restrictions on the use of formaldehyde, it is necessary to develop and implement suitable alternatives to replace formaldehyde-based adhesive systems such as urea formaldehyde in the woodworking industry. This review represents a critical evaluation of formaldehyde-free adhesive systems for the production of particleboard wood composites proposed in the literature so far. The adhesive systems analyzed here include both synthetic and renewable adhesives.